Exploring the diversity of the fungal community in Chinese traditional Baijiu daqu starters made at low-, medium- and high-temperatures. (1st June 2022) - Zhou, Qingfeng; Ma, Kang; Song, Yang; Wang, Ziwei; Fu, Zhongjun; Wang, Yuhong; Zhang, Xiaoyu; Cui, Mingfang; Tang, Ning; Xing, Xiaolong
Abstract: Daqu is a traditional Chinese baijiu starter. To investigate the composition of the microbial community of daqu starters, high-throughput sequencing (HTS) combined with culture-dependent method was used to analyze the fungal diversity of thirty starters made at three temperatures (low-, medium- and high-temperature). In the study, we isolated 420 isolates of fungal strains through the plate culture method. Saccharomyces cerevisiae, Wickerhamomyces anomalus and Saccharomycopsis fibuligera were the most common yeasts encountered in these daqu starters, accounting for 79% of the relative abundance. HTS showed that the dominant genera in low-temperature daqu were distinct from those of medium- and high-temperature. The genera, Thermomyces and Thermoascus, exhibited a higher relative abundance and were considered to be the dominant flora in high-(75%) and medium-(47%) temperature starters, respectively. These two genera were thermotolerant fungi. Saccharomycetaceae was the predominant microflora in low-temperature daqu with a relative abundance of 68%. The present study suggests that the effect of the daqu processing temperature on the fungal community was important and that a knowledge of microbial composition should help to screen fermentation strains thus improving the quality of baijiu liquor. Highlights: Analyzed the fungal composition of three representative Chinese baijiu daqu starters . Effective high-throughput sequencing (HTS) and culture-dependent method resolving the species abundance. Daqu microbial diversity correlated with processing temperature.